Perancangan Standard Operating Procedure (SOP) Departemen Human Resources (HR) Di PT. X - Hadiwiyono, Priscyllia Surya; Panjaitan, Togar W S (Jurnal Titra, 2013)
Human Resources (HR) Department is department which handled all the employeeâs needs from many aspects, which is training, medical, uniform, etc. All employee fulfillments done by a workflow that called Standard Operating Procedure (SOP). HR Department always doing development by doing improvement in fulfillment employeeâs needs and this process happened fast enough that affect to SOP discrepancy between HR sub-Department. There are six SOPâs that is not corresponding between HR sub-Department generates misunderstanding in practice, such as Training, Medical, Uniform, Special Leave, ID Card, Pension Fund SOP. Therefore a new SOP that corresponding is needed to accommodate all the changes that happened. Now the SOP that is not corresponding, in the future needs PIC who responsible to update the SOP by using method and template that already provide so that will be corresponding/uniformity SOP between HR sub-Department.